מה אם g [f (5)] אם (fx) = x + 1 ו- g (x) = 3x-2?

מה אם g [f (5)] אם (fx) = x + 1 ו- g (x) = 3x-2?
Anonim

תשובה:

#g (f (צבע (אדום) (5)) = 16 #

הסבר:

כדי לפתור בעיה זו עליך להחליף תחילה #color (אדום) (f (x)) # או #color (אדום) ((x + 1)) # לכל #color (אדום) (x) # בפונקציה #g (x) #.

#g (צבע אדום) (x)) = 3 צבע (אדום) (x) - 2 # הופ post

# g (צבע (אדום) (f (x)) = 3 (צבע (אדום) (x + 1)) - 2 #

# x) צבע (אדום) (x (x)) = (3 xx צבע (אדום) (x)) + (3 xx צבע (אדום) (1)) - 2 #

#g (צבע (אדום) (f (x)) = 3x + 3 - 2 #

#g (צבע (אדום) (f (x))) = 3x + 1 #

עכשיו, כדי לפתור #g (f (5)) # אנחנו חייבים להחליף #color (אדום) (5) # לכל אחד #איקס# in #g (f (x)) #

#g (f (צבע (אדום) (x))) = 3 צבע (אדום) (x) + 1 # הופ post

# (f (צבע (אדום) (5))) = (3xxcolor (אדום) (5)) + 1 #

#g (f (צבע (אדום) (5)) = 15 + 1 #

#g (f (צבע (אדום) (5)) = 16 #

# "First", f (x) = x + 1 rRrr f (5) = 5 + 1 = 6. #

# G (6) = 3 (6) -2 = 18-2 = # #